IB - "Miller, David (ed.)" (Oxford, 1983)
We know a great deal. And we know not only many details of doubtful intellectual interest but also things which are of considerable practical significance and, what is even more important, which provide us with deep theoretical insight, and with a surprising understanding of the world.
Keywords: "Popper, K. R."